The Impact of Harmful Habits on Academic Performance and Sports Activities among Young People - Yermilova, Victoria; Stroiteleva, Natalia; Egorova, Zhanna; Vanina, Ekaterina (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Smoking and alcohol consumption is a growing trend among young people worldwide. The purpose of this study was to provide students with a comparative analysis of adherence to harmful habits (smoking and alcohol) on the one hand and the frequency of sports and academic performance on the other, taking into account gender differences. The research was conducted in 2019-2020 in 5 cities of Russia; the sample included 1500 people aged 18.4 ± 1.1 years, divided into three equal groups. The control (first) group had students who are not engaged in sports, and the second group comprised students practicing sports but not professionally. The third group was made up of student-athletes. All participants were surveyed to determine the frequency of adherence to harmful habits. In the control group, boys smoked 50% more often than girls (p ≤ 0.05), while in the third group, smoking among boys was registered 70 times less often (p ≤ 0.001). Alcohol consumption in controls was 0.5 times more likely among boys (p ≤ 0.05). Harmful habits affect young people’s free time and reduce their academic performance and ability to practice sports.